Severe KCNT1-related developmental and epileptic encephalopathy - A. G. Malov; L. Yu. Brokhin; A. V. Veselkova (Эпилепсия и пароксизмальные состояния, 2025)
Developmental and epileptic encephalopathy (DEE) caused by a mutation in the KCNT1 gene (KCNT1-DEE) is registered in the Online Mendelian Inheritance in Man (OMIM) catalogue inder code number 614959. Alternative names: DEE 14, early infantile epileptic encephalopathy 14. KCNT1-DEE most often manifests as a syndrome of “epilepsy in infancy with migrating focal seizures”. However, the course of epilepsies due to mutant KCNT1 gene is characterized by a broad clinical polymorphism. The article describes a child with severe KCNT1-DEE with clinical picture dominated by drug-resistant focal seizures, profound mental retardation and spastic tetraparesis, as well as microcephaly and microsomia.